PENGARUH KOMUNIKASI VIRTUAL MELALUI PESAN TEKS TERHADAP KUALITAS HUBUNGAN PERTEMANAN PADA MAHASISWA BARU (Survei Pada Mahasiswa Ilmu Komunikasi UPN "Veteran" Jakarta Angkatan 2021) - Nadiah Hopipah (2022)
The pattern of society communication has totally changed towards virtual communication because of condition Covid-19 pandemic. Virtual communication through text messages provides various obstacles for new students college from Communication Sciences UPN Veteran Jakarta 2021, so that it will affect the quality of friendship relationships that exist between new students. This study aims to determine how huge influence of virtual communication through text message on the new student college from Communication Sciences UPN Veteran Jakarta 2021. Researchers use the theory of Computer Mediated Communication (CMC) as the basis of human interaction through, or technology aid by three core concepts that is, communication, mediated and computer. This study uses the positivism paradigm with explanative quantitative methods, the number of samples is 176 respondents. The result showed that there was a huge significant relationship between virtual communication by text message with coefficient value of 0,541 on the quality of new students friendship. The result of the coefficient of determination indicates that the effect of virtual communication by text message towards the quality of the new student friendship raises 25,2% and the rest percent is influenced by other factor that were not examined in this study. This result is intensified by the result of the hypothesis test, which states that H0 is declined while H1 is accepted, which means there is a significant influence on communication through text message regarding the quality of friendship relationships on the new students from Communication Sciences UPN Veteran Jakarta 2021.